A Testing Apparatus for Gas-Driven Coal and Gas Outbursts and its Application - Zou, Yunlong; Peng, Bo; Liu, Rong; Fan, Jinyang (Frontiers in Earth Science, 2022)
In this study, a multi-physics coal and gas outburst experimental apparatus is developed to allow investigating the gas-driven mechanism behind the disaster caused by coal and gas outbursts in tectonic regions. The apparatus can simulate the coal and gas outbursts under different initial geo-stresses, gas pressures and temperatures. By integrating acoustic emission sensors in the holes on axial platens, acoustic signals from coal samples during the whole test can be monitored. A series of testability experiments were conducted on the developed apparatus to verify its performance. The damage characteristics and outburst occurrence of raw coal under different gas pressures were experimentally studied and that provided a more complete theoretical basis for coal and gas outburst. The degree of fragmentation of coal samples and the mass proportion distributions of the outburst pulverized coal after outbursts under different gas pressures were analyzed, as a reference for exploring the evolutionary characteristics of coal and gas outburst with gas-driven action.